1977
DOI: 10.1002/ana.410020603
|View full text |Cite
|
Sign up to set email alerts
|

Congenital fiber type disproportion in identical twins

Abstract: Eighteen-month-old identical twins with the muscle histological characteristics of congenital fiber type disproportion are reported. The fiber typing system of pH-dependent adenosine triphosphatase was used to analyze the size and percentage of type 1, 2A, and 2B fibers in muscle tissue obtained by needle biopsy. Both twins had significantly larger type 2 than type 1 fibers, with 2B fibers representing the largest type. One patient also had type 1 predominance at the expense of a reduction in 2B (2B deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Extraocular, bulbar, face and neck muscles were preserved in our patients, while involvement of facial muscles, ophthalmoplegia and bulbar or respiratory muscles have been previously reported in up to 35% of mild or moderate CFTD cases and in up to 70% of severe cases (Clarke and North, 2003). CFTD is frequently regarded as a static muscle disorder, without significant deterioration after early childhood and even improvement with age (Brooke, 1973;Curless and Nelson, 1977;Cavanagh et al, 1979). In our patients, however, there was slow but steady progression of weakness.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Extraocular, bulbar, face and neck muscles were preserved in our patients, while involvement of facial muscles, ophthalmoplegia and bulbar or respiratory muscles have been previously reported in up to 35% of mild or moderate CFTD cases and in up to 70% of severe cases (Clarke and North, 2003). CFTD is frequently regarded as a static muscle disorder, without significant deterioration after early childhood and even improvement with age (Brooke, 1973;Curless and Nelson, 1977;Cavanagh et al, 1979). In our patients, however, there was slow but steady progression of weakness.…”
Section: Discussionsupporting
confidence: 51%
“…The characteristic histochemical pattern on muscle biopsy consists of a predominance of type 1 fibres, which are at least 12% smaller than type 2 fibres, the latter being normal or hypertrophic (Brooke, 1973;Fardeau et al, 1975;Cavanagh et al, 1979). Sporadic and familial cases-consistent with both autosomal dominant and recessive inheritance-have been reported (Brooke, 1973;Kinoshita et al, 1975;Curless and Nelson, 1977;Eisler and Wilson, 1978;Jaffe et al, 1988). However, the diagnostic criteria, histopathological features and clinical course of the disease are still insufficiently defined.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review of 39 cases of CFTD, 22 were sporadic, 11 suggestive of autosomal dominant inheritance, and 6 suggestive of autosomal recessive inheritance (2). CFTD has also occurred in both monozygotic and dizygotic twins and in a family with an apparently balanced t(10;17) translocation, further supporting a genetic etiology in at least some instances (7)(8)(9). Most recently, mutations in the alpha actin gene ACTA1 have been identified in some individuals with CFTD (10).…”
mentioning
confidence: 99%
“…Some patients may have delayed onset with mild symptoms, mainly muscle pain (3). In some families, studies of affected siblings suggest an autosomal recessive pattern of inheritance (4). Other studies have shown parental involvement pointing to an autosomal dominant mode of inheritance (5,6).…”
mentioning
confidence: 99%